Implementasi Kewajiban Sertifikasi Halal bagi UMKM di Kota Banjarmasin - Nahdhah, Nahdhah; Riswandie, Iwan (Interdisciplinary Explorations in Research Journal, 2024)
ABSTRACT Halal certification is important because the majority of Indonesia's population is Muslim so the halalness of the products consumed is a major concern. Even though the government has established regulations through Law Number 33 of 2014 concerning Halal Product Guarantees which was updated with the Job Creation Law of 2020, many MSMEs have not fully implemented them, especially the city of Banjarmasin. The method used is an empirical research method with the research object being MSMEs located in Banjarmasin City, East Banjarmasin District. Research identifies factors inhibiting implementation, including lack of outreach and education, cost constraints, and limited supporting infrastructure. The results of this research recommend the need to increase socialization, technical support and mentoring so that MSMEs can meet halal standards more easily and increase competitiveness. Keywords: Implementation, Halal Certification, MSMEs   ABSTRAK Sertifikasi halal menjadi penting karena mayoritas penduduk Indonesia beragama Islam sehingga kehalalan produk yang dikonsumsi menjadi perhatian utama. Meskipun pemerintah telah menetapkan regulasi melalui Undang-Undang Nomor 33 Tahun 2014 tentang Jaminan Produk Halal yang diperbarui dengan Undang-Undang Cipta Kerja Tahun 2020, banyak UMKM belum sepenuhnya menerapkannya khususnya kota Banjarmasin. Metode yang digunakan adalah metode penelitian empiris dengan objek penelitian UMKM yang berada di Kota Banjarmasin Kecamatan Banjarmasin Timur. Penelitian mengidentifikasi faktor-faktor penghambat implementasi, termasuk kurangnya sosialisasi dan edukasi, kendala biaya, dan keterbatasan infrastruktur pendukung. Hasil penelitian ini merekomendasikan perlunya peningkatan sosialisasi, dukungan teknis, serta pendampingan agar pelaku UMKM dapat memenuhi standar kehalalan dengan lebih mudah dan meningkatkan daya saing. Kata Kunci : Implementasi, Sertifikasi Halal, UMKM